Nanosized κ-Carbide and B2 Boosting Strength Without Sacrificing Ductility in a Low-Density Fe-32Mn-11Al Steel - Changwei He; Yongfeng Shen; Wenying Xue; Zhijian Fan; Yiran Zhou (Nanomaterials)
High-performance lightweight materials are urgently needed because of energy savings and emission reduction. Here, we design a new steel with a low density of 6.41 g/cm3, which is a 20% weight reduction compared to the conventional steel. The mechanical properties and microstructures of the steels prepared with different routes are systematically explored by utilizing uniaxial tensile testing and transmission electron microscopy. The steel processed by cold rolling and recrystallization annealing at 950 °C for 15 min shows an ultra-high yield strength of 1241 ± 10 MPa, while retaining a good ductility of 38 ± 1%. The high yield strength is mainly related to the synergistic precipitation strengthening introduced by nanoscale B2 and κ′-carbides. It is encouraging to notice that the yield strength increased without scarifying ductility, compared to the ST steel. The key reason is that the high strain hardening rate is activated by combined factors, including the blockage of numerous twins and nanoscale B2 to the dislocation movements, and dynamic slip band refinement. This study is instructive for concurrently enhancing the strength and ductility of austenitic lightweight steels with fully recrystallized grains and dual nano-precipitates.